Consumer basket working man as a factor influencing the development of production democracy - Oleksandr Shemyakov (Cхід, 2013)
In the article the estimation of the state a consumer to the basket of working man is given in Ukraine. The lacks of operating practice of forming of living wage and their influence are examined on upgrading of labour life of man. Intercommunication is set between upgrading of labour life by development of production democracy.